APPLICATION OF THE ASSISTED DISCOVERY LEARNING MODEL ANIMATION VIDEO MEDIA ON THE LEARNING OUTCOMES OF PANCASILA EDUCATION IN CLASS IV STATE ELEMENTARY SCHOOL NGADIREJO - Sindy Rupianingsih; Hamdan; Cahyo Dwi Andita (International Journal of Educational Review, 2026)
This study aims to determine the learning outcomes of Pancasila Education for grade IV students of SD Negeri Ngadirejo after the implementation of the Discovery Learning Model Assisted by Animation Videos is significantly complete. The background of this research is based on the low learning outcomes of students due to the lack of active involvement of students in learning and learning methods that are still monotonous and teacher-centered. The research method used is quantitative with One Group Pre-test and Post-test design. Samples were taken from one class, namely in grade IV with a total of 23 students. The research instrument is in the form of a multiple-choice test that has been tested for validity and reliability. Based on the results of the research and discussion, it was obtained that the average pre-test score was 49.4 and there were 19 students who did not achieve the KKTP score or < 70 so that it was declared incomplete and only 4 students completed. Meanwhile, after receiving treatment, the results of the posttest were obtained with an average score of 84.9, there were 20 students who achieved completeness and reached a score of 70 and 3 students did not complete. Thus, it can be concluded that the Discovery Learning Model Assisted by animated videos is effective in improving the learning outcomes of Pancasila Education for grade IV students. This learning model is recommended to be implemented as a fun alternative to active learning in elementary school.